Dinamika Pertumbuhan Feminisme Di China Dalam Perspektif Konstruktivisme - Anna Yulia Hartati; Ismiyatun Ismiyatun; Adi Joko Purwanto; Nur Islamiati (LP2M, 2021)
This article describes how the growth process of feminism in China in the perspective of constructivism regarding the life-cycle of norms. In theory, there are three stages of how a norm which in this case is feminism through the life-cycle of norms. This research method uses a qualitative method of literature study. In this article, the findings are that there are three propositions related to the emergence of international norms in feminism in China, the first is Norm emergence which is described by the emergence of one of the famous female figures, namely, He Zhen, who adopted western feminism by not leaving Chinese cultural identity which was considered good for her. Chinese women's social change. In contrast to other reformers, He Zhen specifically separates the case of feminism from nationalism, stating that women's liberation is not for the sake of the nation, but rather a moral necessity. Second, the Norm Cascade is illustrated by the influence of China's state ratification of the Convention Elimination of All Forms of Discrimination against Women (CEDAW) held in Copenhagen Denmark, by accepting international norms on gender equality which in turn will require domestic laws to make some changes to suit the issue. Third, Internalization is described by the growth process of Chinese feminism, namely the process of fusion with culture within the body of feminism itself, or in other words, feminism that develops has its own unique characteristics that are not owned by other countries and only China has it.